Identification of Chemical Compounds of Ylang Ylang Flower Essential Oil (Cananga Odorata) and Kaffir Lime Essential Oil (Citrus Hystrix) Using Gas Chromatography- Mass Spectrophotometry (Gc-Ms) - Wibawanto, Dhea Setyalova; Anwar, Yelfi; Muryanto, Muryanto (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Essential oils are substances that have an aroma contained in plants, these oils are usually also referred to as volatile oils and are usually in liquid form and can be isolated from plant parts such as roots, stems, leaves, flowers, fruit and seeds. This research aims to determine the chemical components of kaffir lime essential oil (Citrus hystix), ylang ylang (Cananga odorata) using the GC-MS method. The conclusion from the research results is that there is a main compound produced by kaffir lime (Citrus hystix) essential oil, namely the chemical compound D-limonane (15.15%) while the chemical compound linalool contained in kaffir lime (citrus hystrix) essential oil is only 1.04 % so that the essential oil of kaffir lime (citrus hystrix) does not meet the quality standard requirements for the chemical compound linalool of 3.5-5.5%. The main compound produced by ylang-ylang oil (Cananga odorata) is the chemical compound Linalool (17.85%). In this case, efforts need to be made to improve the quality of essential oils in order to increase added value and meet the requirements for essential oil quality standards.